2006
DOI: 10.1143/jjap.45.l852
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Microstructures in the Longitudinal Direction of Very Narrow Cu Interconnects

Abstract: We have succeeded in observing the longitudinal microstructure of very narrow Cu interconnects for the first time. We found that the average grain sizes along the longitudinal direction of Cu interconnect trenches increased with increasing line width, and they were 278 nm for 80 nm, 303 nm for 100 nm, and 346 nm for 180 nm wide interconnects. Ratios of the average grain size to line width were 3.5 for 80 nm, 3.03 for 100 nm, and 1.9 for 180 nm line widths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…15) To clarify the grain sizes and their distributions inside the Cu interconnects with line widths of 50 nm, we investigated the cross-sectional microstructures in the longitudinal direction of the Cu wires using a focused ion beam (FIB) instrument (Hitachi FB-2000A). 14) Before FIB milling, 100-nm-thick carbon films were evaporated onto the samples to protect the Cu wires from damage during milling. Ga þ ion beams accelerated at 30 kV were rastered along the Cu wires to cut holes on both sides precisely at the object portion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…15) To clarify the grain sizes and their distributions inside the Cu interconnects with line widths of 50 nm, we investigated the cross-sectional microstructures in the longitudinal direction of the Cu wires using a focused ion beam (FIB) instrument (Hitachi FB-2000A). 14) Before FIB milling, 100-nm-thick carbon films were evaporated onto the samples to protect the Cu wires from damage during milling. Ga þ ion beams accelerated at 30 kV were rastered along the Cu wires to cut holes on both sides precisely at the object portion.…”
Section: Methodsmentioning
confidence: 99%
“…Observations using field emission transmission electron microscopy (FETEM) techniques revealed that larger grains are predominant in the top part, and smaller grains are predominant in the bottom part of Cu trenches. 14,15) We assume sidewall-restricted grain growth at the bottom of narrow trenches, resulting in grain size distributions in the depth direction of the trench. The grain growth processes of a Cu interconnect strongly depend on trench widths, so the resistivity of next generation Cu interconnects using the 32-nm technology node (50-nm line width) is expected to increase further.…”
Section: Introductionmentioning
confidence: 99%
“…8) However, grain sizes change appreciably from the bottom to the top surface of the Cu wires and TEM observations of Cu wire sectioned along the longitudinal direction, i.e., direction of current flow, have shown that the average grain size at the top is much larger than that at the bottom. 9,10) This trend becomes remarkable as the wire width becomes narrower, because the grain growth near the bottom is likely to be restricted by the trench sidewall. Therefore, the average grain size obtained by conventional observation methods would not reflect on the EM resistance of very narrow Cu wires (< 100 nm).…”
Section: Introductionmentioning
confidence: 99%
“…However, line width dependence of EM resistance and activation energy as a function of average grain size along the longitudinal direction of these Cu wires has not been clarified to date. We have established a technique to evaluate the average grain size when sectioned along the longitudinal direction, 9,10) i.e., direction of current flow in very narrow Cu wires. Then, in this paper, first we evaluate the EM resistance and activation energy as a function of line width, and second, we investigate the influence of average grain size along the longitudinal direction of very narrow Cu wires (< 100 nm) on EM resistance and activation energy to identify the suitable microstructure in the Cu wire with high EM resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive data have been published [1][2][3][4] on the microstructure of damascene Cu lines regarding the grain texture and size distribution and their variations with different line widths. Nevertheless, only few results have been reported recently [5][6][7][8] on the microstructures of Cu lines narrower than 100 nm. For ultra-narrow Cu lines less than 100 nm wide, the resistivity was found to increase as the line width scales down.…”
Section: Introductionmentioning
confidence: 99%